HIV incidence and risk factors among transgender women and cisgender men who have sex with men in two cities of China: a prospective cohort study - Duo Shan; Zhen Ning; Maohe Yu; Huang Zheng; Jie Yang; Hui Gong; Jian Li; Hui Liu; Lu Liu; Vania Wang; Xiong Ran; Mengjie Han; et al. (BMC, 2022)
Abstract Background HIV epidemic among men who have sex with men (MSM) remains a major public health concern in China. Despite a growing body of research on transgender women worldwide, little is known about Chinese transgender women within MSM. We sought to estimate HIV incidence and distinguish risk factors of HIV acquisition among them from that among cisgener (non-transgender) MSM (cis-MSM). Methods We conducted an open cohort study among Chinese MSM, including those who were identified as transgender in Shanghai and Tianjin. Participants were initially recruited by local community-based organizations from January to June, 2016, and were followed up approximately every 6 months until June 2018. At each visit, a structured questionnaire was used to gather information on demographics, sexual risk behaviors, and HIV status. HIV incidence was calculated as the number of seroconversions divided by total number of person-years of follow-up among HIV-negatives at baseline. Risk factors of HIV acquisition were assessed by univariate and multivariate Cox regression models with time-dependent variables. Results A total of 1056 participants contributed 1260.53 person-years (PYs) of follow-up, 33 HIV seroconversions occurred during the follow-up period, yielding an estimated HIV incidence of 2.62 (95% CI 1.80-3.68) per 100 PYs. HIV incidence among transgender women was 4.42 per 100 PYs, which was significantly higher than that of 1.35 per 100 PYs among cis-MSM, demonstrating a threefold higher odds of HIV infection than cis-MSM. For transgender women, those lived locally ≤ 2 years (adjusted hazard ratio [aHR] = 1.76, 95% CI 1.13-2.76) and unprotected anal sex last time (aHR = 4.22, 95% CI 1.82-9.79) were more likely to acquire HIV. For cis-MSM, factors associated with HIV acquisition were frequency of anal sex ≥ 3 times in past one month (aHR = 4.19, 95% CI 1.06-16.47) and unprotected anal sex last time (aHR = 5.33, 95% CI 1.52-18.73). Conclusions Compared to cis-MSM, transgender women were at higher risk of HIV acquisition, highlighting an urgent need of tailored prevention. Future HIV program should consider to include them to ensure that this population in China are not left behind. Graphical abstract